2021
DOI: 10.7759/cureus.12923
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Falls and Fractures in Alzheimer’s Patients Compared to General Population

Abstract: Introduction Alzheimer's disease (AD), found in the aging elderly population, is a progressive neurodegenerative disorder that leads to worsening memory loss and cognitive impairment. Falls and fractures are common in the overall elderly population. Hence, the purpose of this study is to determine the prevalence of falls and fractures in Alzheimer's patients compared to the general population. Methodology This longitudinal study was conducted at the neurology outpatient department (OPD) in a tertiary healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…AD patients are more susceptible to falls and fractures, which often result from reduced skeletal muscle and bone strength. (14,15) Therefore, understanding the mechanisms underlying bone and muscle loss in AD will be critical for finding therapeutic targets that could effectively reduce falls and fractures by targeting both tissues. Further, defining a potential mechanism of bone and muscle loss independent of central neurodegeneration will improve the overall understanding of neurodegenerative effects on peripheral physiology.…”
Section: Introductionmentioning
confidence: 99%
“…AD patients are more susceptible to falls and fractures, which often result from reduced skeletal muscle and bone strength. (14,15) Therefore, understanding the mechanisms underlying bone and muscle loss in AD will be critical for finding therapeutic targets that could effectively reduce falls and fractures by targeting both tissues. Further, defining a potential mechanism of bone and muscle loss independent of central neurodegeneration will improve the overall understanding of neurodegenerative effects on peripheral physiology.…”
Section: Introductionmentioning
confidence: 99%
“…For MCI, the cognitive status of the participants was determined by various cognition assessment tools (e.g., the Mini-Mental State Exam [ 62 ], Montreal Cognitive Assessment [ 63 ], Frontal Assessment Battery [ 64 ], etc.). The average participant age spanned from 65 [ 34 ] to 86.6 [ 43 ] years for the AD participants, and from 69.5 [ 51 ] to 81.1 [ 55 ] years for MCI participants. All included studies tracked fall prevalence or the number of fallers during a 12-month period (either retrospectively or prospectively).…”
Section: Resultsmentioning
confidence: 99%
“…According to fall prevalence, its rate was 37 (30.8%), which in the study of Dev et al showed that this rate in the group of Alzheimer's patients 32 (22.8%) for a minimum of one fall, prevalence 8 (5.7%) multiple falls and a prevalence of 18 (12.8%) have been reported for non-vertebral fractures (22). In the paper of Kato-Narita et al, the prevalence of falls in AD patients was 55% (36), in the study of Soysal et al on dementia patients, the prevalence of fear of falling was 86.9% in patients with dementia and 36.0% in patients with AD (37).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, when these disabilities are associated with dementia, this function becomes weaker and may even lead to the patient falling (16). Falls are one of the most important causes of fatal and non-fatal injuries in people over 64 years of age, which has high prevalence and many consequent injuries, and this shows the importance of the issue (22).…”
Section: Introductionmentioning
confidence: 99%